Amelioration of Systemic Fibrosis in Mice by Angiotensin II Receptor Blockade. Issue 5 (23rd April 2013) - Marut, Wioleta; Kavian, Niloufar; Servettaz, Amélie; Hua‐Huy, Thong; Nicco, Carole; Chéreau, Christiane; Weill, Bernard; Dinh‐Xuan, Anh Tuan; Batteux, Frédéric
Abstract: Objective: Systemic sclerosis (SSc) is characterized by microvascular damage, fibrosis of skin and visceral organs, and autoimmunity. Previous studies have shown that angiotensin II is involved in the synthesis of type I collagen. We investigated whether the blockade of angiotensin II receptor type I (AT1 ) by irbesartan reduces skin and lung fibrosis in 2 murine models of SSc. Methods: SSc was induced by daily intradermal injection of HOCl into the backs of BALB/c mice (HOCl‐induced SSc). Mice were treated daily with irbesartan by oral gavage. Results: Irbesartan reduced dermal thickness, collagen concentration, Smad2/3, and α‐smooth muscle actin expression, as well as fibroblast proliferation and H‐Ras expression in the skin of mice with HOCl‐induced SSc. Mice treated with irbesartan also displayed less lung fibrosis, less inflammation, and a lower concentration of collagen in the lungs than untreated mice. Exhaled nitric oxide, inducible nitric oxide synthase, and 3‐nitrotyrosine expression in the lungs were decreased following irbesartan treatment. Moreover, irbesartan reduced the number and the proliferation of splenic B and T cells and the serum levels of anti–DNA topoisomerase I autoantibodies. Conclusion: Irbesartan, an AT1 antagonist, prevents fibrosis and inflammation and inhibits nitric oxide production in HOCl‐induced models of systemic fibrosis. Our findings extend the indication of an AT1 antagonist to SSc patients with diffuse fibrosis, especially those with lung involvement.